Prototype of an adaptive wiper system for electric vehicles for disabled users using a servo motor - Raihan Bayu Nugroho; I Wayan Warsita; I Wayan Adiyasa (Journal of Automotive and Mechanical Applied Technology, 2025)
This study presents the design and implementation of a prototype wiper system using a servo motor, specifically developed for electric vehicles designed for persons with disabilities. The system is structured through several stages, including the creation of a wiring diagram, the development of a control system based on an Arduino Uno microcontroller, and the integration of key components such as a 12V battery, a three-position switch, a step-down LM2596 module, and an RDS3239 servo motor. The control logic enables two-speed wiping modes low and high regulated by user input via the switch. Electrical testing demonstrated that the current drawn by the system was 0.26 A at low speed and 0.37 A at high speed, with corresponding power consumption of 3.12 W and 4.44 W, respectively. These values fall within safe operating limits, indicating energy efficiency suitable for electric vehicle applications. Motion testing showed that the system achieved 30 wipes per minute at low speed and 60 wipes per minute at high speed, with the high-speed mode meeting the minimum functional criteria set by national standards. Angular deviation analysis further revealed that increased speed slightly impacted sweep precision, though still within acceptable tolerances. The results indicate that the developed system not only performs effectively in varying operational conditions but also offers energy-efficient and responsive functionality. This makes it a viable solution for adaptive and accessible mobility technologies in electric vehicles for persons with disabilities.